Theater of operations the Gulf Wars 1991-2011 - Eleey, Peter ca. 20. Jh; Katrib, Ruba 1982- (MoMA PS1, 2019)
"The 1991 Gulf War marked the start of a lengthy period of American-led military involvement in Iraq that led to more than a decade of sanctions, the 2003 Iraq War, and ongoing repercussions throughout the region. Though the Iraq War officially ended in 2011, artists have continued to examine these conflicts and their impacts. Theater of Operations: The Gulf Wars 1991-2011 charts the effects of these wars on cultural production in Iraq and throughout its diasporas, as well as responses to the wars in the West, revealing how this period was defined by unsettling intersections of spectacularized violence and new imperialisms. The exhibition features more than 80 artists and collectives, including Afifa Aleiby, Dia al-Azzawi, Thuraya al-Baqsami, Paul Chan, Harun Farocki, Guerrilla Girls, Thomas Hirschhorn, Hiwa K, Hanaa Malallah, Monira Al Qadiri, Nuha al-Radi and Ala Younis. -- This catalog features newly commissioned essays by Zainab Bahrani, Rijin Sahakian, Nada Shabout and McKenzie Wark alongside texts by exhibition co-curators Peter Eleey and Ruba Katrib. Excerpts from period journals by artist Nuha Al-Radi and anonymous blogger Riverbend detail life in Iraq over two decades of war, sanctions and occupation. Reprinted essays from Jean Baudrillard and Serge Daney provide additional context, delving into the effects of the conflict upon media and visual culture."--From distributor
Rückseite Titelblatt: Catalogue of an exhibition at MoMA PS1, Long Island City, New York, November 3, 2019-March 1, 2020
Paralleltitel in arabischer Sprache auf Cover: Masraḥ al-ʻamalīyāt : Ḥurūb al-Khalīj
Contributors: Peter Eleey, Ruba Katrib, Zainab Bahrani, Jean Baudrillard, Serge Daney, Nuha al-Radi, Riverbend, Rijin Sahakian, Nada Shabout, McKenzie Wark
Keywords: Medien; Golfkrieg -- 1990-1991; Kunst; Golfkrieg -- 2003; Persian Gulf War, 1991 / Exhibitions; Persian Gulf War, 1991 / Art and the war / Exhibitions; Iraq War, 2003-2011 / Exhibitions; Iraq War, 2003-2011 / Art and the war / Exhibitions; War in art / Exhibitions; Art, Modern / 21st century / Exhibitions; Iraq War (2003-2011); Persian Gulf War (1991); War in art; Iraq; 1991-2011; Exhibition catalogs; Ausstellungskatalog -- MoMA PS1 -- 03.11.2019-01.03.2020 -- Long Island City, NY